Microbes in agriculture and environmental development - Singh, Chhatarpal; Tiwari, Shashank, Dr.; Singh, Jay Shankar; Yadav, Ajar Nath (Boca Raton, FL : CRC Press, 2021)
"This edited book explores the applications of microbes for the improvement of environmental quality and agricultural productivity through microbial inoculants and enzymes, useful for the conservation and restoration of degraded agro and natural ecosystems, crop yield extension, soil health improvement and so forth. It discusses wastewater treatment and recycling of agricultural and industrial wastes as effective uses of microbial technology. It provides detailed impressions of recent trends in microbial application in plant growth promotion, soil fertility, microbial biomass and diversity and sustainable environment through bioremediation, biodegradation, and biosorption processes"--
Plant Microbe Association Leading to Sustainable Agro-Ecosystem -- Soil Quality Monitoring in Selected Regions of Raebareli, Uttar Pradesh and Rela Tionship of Microbes in Soil Fertility Management -- Biofertilizers in Boosting Agricultural Production -- Bio-fertilizers for Management of Soil, Crop and Human Health -- Crop Residue Burning and its Effects on Environments and Microbial Communities -- Bioconversion of Solid Organic Wastes and Molecular Characterization of Bacterial Population during the Decomposition Process -- Beneficial Soil Microflora for Enhancement in Crop Production and Nutritive Values in Oil Containing Nuts -- Fungal Amylases for Detergent Industry -- Plant Growth Promoting Rhizobacteria (PGPR) Activity in Soil -- Nisin in Food Packaging -- Application of Genetically Engineered Microbes for Sustainable Development of Agro-Ecosystem -- Interaction Scenario of Insect -- Plant and Mycorrhizal Fungi -- Tannery Wastewater: a major source of residual organic pollutants and pathogenic microbes and their treatment strategies -- Role of Microbes in Bioremediation of Pollutants (Hydrocarbon) in Contaminated Soil.
OCLC-licensed vendor bibliographic record.
Keywords: Soil microbiology; Microbial ecology; Crop residue management; Biofertilizers; Bioremediation; Microbial biotechnology; SCIENCE / Environmental Science; SCIENCE / Life Sciences / Biology / Microbiology; TECHNOLOGY / Agriculture / Forestry